(untitled) (Вісник: Міжнародні відносини, 2025)
After the full-scale invasion of Ukraine by Russia in 2022, Ukraine’s foreign policy subjectivity underwent qualitative changes. The state moved from a reactive role to the position of an initiator of international processes, accompanied both by spontaneous international solidarity and by managed diplomatic actions. Purpose of the study – to conceptualize the hybrid nature of Ukraine’s foreign policy influence and to propose an analytical model that combines its symbolic and institutional dimensions. Results. Two main dimensions of influence have been identified: spontaneous (organic) and institutional (managed). Using discourse analysis and a literature review, it is described how Ukraine combines emotional-symbolic capital and structured diplomacy to form a new international presence. A methodological approach to influence assessment is proposed, integrating narrative analysis, media indexing, and the concept of symbolic capital. Conclusions. The modern international subjectivity of Ukraine is formed at the intersection of value legitimacy, diplomatic initiative, and hybrid communication strategies.